BIOLOGY AND INTRINSIC GROWTH RATE OF EARWIG (Euborellia annulata) - Nurnina Nonci (Indonesian Journal of Agricultural Science, 2005)
Earwig (Euborellia annulata) is a potential predator of corn borer (Ostrinia furnacalis), one of the most important pests of corn. To include the use of predator in integrated pest management (IPM) to control the pest, it is necessary to understand the basic information of the predator. This study aimed to know biology and intrinsic growth rate of the predator feed on an artificial media (dog food). Ten pairs of newly emerging adults of the predator were placed in a small plastic container containing a mixture of soil and sand (1:1 v/v) supplemented with an artificial food. The average temperature and relative humidity during the study were kept at 27.9-30.3oC and 76.7-92.3%, respectively. The biological aspects of the predator evaluated were number of eggs laid, hatched, and died, as well as its oviposition period and adult mortality. The intrinsic growth rate was studied from a group of 200 newly laid eggs and results were analyzed based on the method of Birch. The biological aspects study showed that number of eggs laid by a single female of E. annulata was 86-166, which were laid five times in a group of 9-45 eggs. The nymph consists of five instars. Length of nymphs varied ranging from 4 to 13 mm depends on their instar. The fifth instar nymph period was 4-6 days for female and 2-3 days for male. The period of first mating was shorter; the shortest was 2 minutes and the longest one was 70 minutes. Both male and female were able to do mating several times at an interval of several seconds or minutes. Pre-oviposition period was 6-13 days. The eggs were deposited five times, the first, second, third, fourth, and fifth oviposition period were 7-22 days, 7-21 days, 7-18 days, 11-18 days, and 11-21 days, respectively. The oviposition period was 32-59 days and postoviposition period was 21-51 days. Ratio between male and female was 1.4:1.0. The average natural mortality of E. annulata was 10.5% which means that 89.5% of deposited eggs hatched became nymphs. The study also revealed that the intrinsic growth rate (r) of the predator was 0.0772, net reproductive rate (R0) 80.16, limited growth rate (λ) 1.17, nymph stage period 39-46 days, and adult longevity of male and female were 57-75 and 61-89 days, respectively. The study implies that E. annulata is potential to be incorporated in IPM for controlling corn borer.